GAGAUZIA: ROAD TO INDEPENDENCE OR maintaining the status quo? - L. . Donaj; O. E. Grishin (Проблемы постсоветского пространства, 2017)
Gagauzia is not an independent state. The article focuses on this issue due to the dynamic development of the political situation in the Republic of Moldova and the international situation. The authors try to present the problem of the functioning of the Authority's and assess future. To do this historical digression, showing the conditions under which formed the Gagauz autonomy. The authors do historical digression and show the condition under which was formed the Gagauz autonomy. In the article are analyzed the important factors determining events in the region, the interests of external actors - the European Union, Romania, Turkey and Russia. The authors examine media reports and give political commentary about what is happening in Gagauzia, often contrasting, which can correct some erroneous, black-and-white picture of the situation.